2004
DOI: 10.1097/01206501-200412000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Contact Allergy and Dermatitis from Methylisothiazolinone after Contact with Wallcovering Glue and after a Chemical Burn from a Biocide

Abstract: Skin exposure to biocides containing high concentrations of methylchloroisothiazolinone/methylisothiazolinone (MCI/MI) may cause severe chemical burns and may also induce sensitization. We report two cases in which skin exposure to a newly launched biocide containing 2-methyl-4-isothiazolin-3-one (MI) and 1,2-benzisothiazolin-3-one led to sensitization to MI, which in the second case was preceded by a chemical burn. A study was performed to investigate the pattern of reactivity to MCI and MI in two patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 7 publications
3
29
0
2
Order By: Relevance
“…Most often, the first cases of contact dermatitis are occupational, whereas consumer cases seem to appear later. Therefore, recent observations of occupational contact dermatitis to MI may be the beginning of an emerging epidemic and should be followed closely (73,74). Furthermore, there is a latency period from the first cases are described until the contact allergy epidemic is recognized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most often, the first cases of contact dermatitis are occupational, whereas consumer cases seem to appear later. Therefore, recent observations of occupational contact dermatitis to MI may be the beginning of an emerging epidemic and should be followed closely (73,74). Furthermore, there is a latency period from the first cases are described until the contact allergy epidemic is recognized.…”
Section: Discussionmentioning
confidence: 99%
“…So far, 2 industrial reports indicate that MI holds a potential for eliciting and probably inducing contact allergy in humans (73,74).…”
Section: Formaldehydementioning
confidence: 99%
“…5 However, cases of sensitization to MI alone were subsequently reported. The first cases of sensitization to MI in industrial products were reported in 2004 and 2006 6,7 ; the first cases of allergic contact dermatitis to MI in cosmetic products were reported in 2010. 8 The currently used patch test (Kathon CG) contains a 3:1 mix comprising MCI (1.125%) and MI (0.375%), magnesium nitrate, magnesium chloride, and water.…”
Section: Introductionmentioning
confidence: 98%
“…Ovdje, opet, STL ima ograničenu uporabu u istraživanju nadražujućeg kontaktnog dermatitisa. Stoga procjena izloženosti predstavlja složen postupak, koji često uključuje i obilazak radnog mjesta, po mogućnosti proveden u zajedničkom djelovanju multidisciplinarnog tima specijaliste medicine rada (i sporta) i struč-njaka zaštite na radu (Lundov et al, 2011., Kaae et al, 2012., Thyssen et al, 2006.,Geier et al, 2004., Henriks-Eckerman et al, 2008., Espasandin-Arias, Goossens et al, 2014., Isaksson et al, 2004., Mose et al, 2012., Bregenbak et al, 2013., Kaur-Knudsen et al, 2012., AaltoKorte et al, 2007., Tong, 1995.…”
Section: Raspravaunclassified